FRI0448 Evaluation of suppurative hidradenitis in patients with chronic arthritis treated with full and tapered biological disease-modifying antirheumatic drugs. (15th June 2017) - Valor, L; Hernández-Flόrez, D; del, T Río; B, JG Ovalles; Barrio, J Martínez; Janta, I; Serrano, B; Nieto, JC; Plaza, M Correyero; Montoya, L Garcia; González, C; Lόpez-Longo, FJ; et al.
Abstract : Background: Suppurative Hidradenitis (SH) is an inflammatory skin disease which often responds poorly to treatment. It is a disorder of the apocrine glands (axillary, inguinal and anogenital regions) that can result in infection, inflamed nodules, cysts, abscesses and sinus tracts. There is a 1–4% incidence of SH in patients with spondyloarthropathies and inflammatory bowel disease, possibly due to innate immune system deregulation. The use of biological disease-modifying antirheumatic drugs (bDMARD), specifically tumor necrosis factor inhibitors, has been useful in cases when other therapies fail. Objectives: To evaluate the prevalence of SH using the SH-questionnaire in bDMARD-treated chronic arthritis patients. Methods: This cross-sectional study included 325 patients diagnosed with chronic arthritis. Patients were recruited consecutively from the Biological Therapy Unit of the Hospital General Universitario Gregorio Marañόn and evaluated from January to March of 2015. All patients had been undergoing full or tapered bDMARD treatment for at least 1 year and none had any history of SH. Those patients deemed to be in clinical remission were on tapered bDMARD dosage. All patients self-completed the validated SH-questionnaire (1) which was considered positive when one answer was affirmative and when lesions presented in >1 anatomical location. Patient pathologies were subclassified into 2 groups: i) peripheral arthritis (PerAR) which includes rheumatoid arthritis (RA), psoriatic arthritis (PsA) and peripheral spondyloarthropathies (PerSpA); ii) axial spondyloarthropathies (AxSpA). Clinical evaluation was performed by the same physician for all patients. Demographic, clinical and laboratory variables were recorded and disease status was assessed through the relevant clinical index, i.e.DAS28-ESR, DAS28-CRP, SDAI, CDAI, BASDAI, BASFI, ASDAS-CRP. Results: SH-positive was observed in 25/325 (7.7% vs. 92.3%) patients. Of these 25 patients, 12 (48%) were female and 13 (52%) male. Mean age was 52 years (SD±12.9) and mean time since diagnosis was 14 years (SD±9.3). Twenty-four out of 25 patients were undergoing anti-TNF treatment (ETN=10, GOL=7, ADL=6, CTZ=1). Eighty-four per cent of patients were undergoing full bDMARD dosage with the remaining 16% on tapered. By subset pathology, 13 SH positives were PerAR type and 12 were AxSpA (5.8% vs. 11.8%, p=0.062). On analysis of PerAR subtypes, we found 6 patients had PsA and 5 RA. Evaluating clinical disease activity, we found 9/13 patients in the PerAR group to be in clinical remission according to DAS28-ESR and CDAI (p=0.02 for both). Additionally, we found only 4/12 patients in remission in the AxSpA group as defined under BASDAI, BASFI and ASDAS-CRP (p=0.006, p=0.005, p=0.004, respectively). Conclusions: We found more SH-positives in the AxSpA than in the PerAR group, which is consistent with published data. A bDMARD tapered dosage was related to SH-positivity which might be linked to persistent and undetectable chronic inflammation. References: Esmann S, et al. Br J Dermatol. 2010 Jul;163(1):102–6. Disclosure of Interest: None declared